Razer / Muhammad Akram Ismail - Ismail, Muhammad Akram (2022)
Gaming laptops, cellphones, and PC accessories such as mice, audio players, keyboards, mouse pads, and gaming chairs are among Razer's most popular items. Razer also released Razer Comms, a voice-over-internet-protocol (VOIP) programme. In terms of sales volume, the Razer DeathAdder gaming mouse is the company's most popular product. Approximately 5% of professional gamers use Razer mouse. Predatory or poisonous species are named after snakes (mice), insects (mouse mats), arachnids (keyboards), marine animals (audio), and felines (audio) (console peripherals). The Razer Blade and Razer Edge laptops, which are named after bladed objects, are the only exceptions. The goal of this project is to figure out what the product's flaw is. Razer is the company that I have selected. For this review, I choose the Razer BlackShark V2 from the company's different goods. In this case study, I used a SWOT analysis to determine the Razer BlackShark V2's strengths, weaknesses, opportunities, and threats. Inconsistent bass and treble output is the biggest issue I found with this device. Increased noise isolation performance on headsets is the best solution to this problem.